Inter State Marriage Trends and Their Relevance to Domestic Harmony: A Study in Sambas West Kalimantan - Asman, Asman; Aamer, Mohammaed (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2026)
The phenomenon of inter-country marriage is one of the social trends that is growing rapidly in various border areas, including in Sambas Regency, West Kalimantan, which borders Malaysia directly. This interstate marriage is not only about administrative and civic aspects, but also has implications for domestic life, especially in terms of harmony, religious values, and culture. This study aims to examine the trend of interstate marriage in the Sambas region and analyze its relevance to domestic harmony in the perspective of Islamic Family Law. This study uses a qualitative approach with field study methods, in-depth interviews, and documentation of transnational married couples, and local religious leaders. The results of the study show that the main motives for interstate marriage in Sambas include economic factors, the openness of border areas, and social and cultural relations that have been established for a long time. However, in practice, intercountry marriages often face serious challenges such as cultural differences, worship practices, maintenance obligations, and marriage legal status that is not always clear nationally or internationally. From the perspective of Islamic Family Law, domestic harmony is highly dependent on the principles of mawaddah, rahmah, and shared responsibility between husband and wife, which must be built on an understanding of religious values and a strong commitment. Therefore, legal regulation and the development of cross-border premarriage are urgently needed so that interstate marriage does not become a source of conflict, but rather strengthens family ties and Islamic values in the midst of globalization dynamics. [Fenomena perkawinan antar negara menjadi salah satu tren sosial yang berkembang pesat di berbagai wilayah perbatasan, termasuk di Kabupaten Sambas, Kalimantan Barat, yang berbatasan langsung dengan Malaysia. Perkawinan antar negara ini tidak hanya menyangkut aspek administratif dan kewarganegaraan, tetapi juga membawa implikasi terhadap kehidupan rumah tangga, khususnya dalam hal keharmonisan, nilai-nilai agama, dan budaya. Penelitian ini bertujuan untuk mengkaji tren perkawinan antar negara di wilayah Sambas serta menganalisis relevansinya terhadap keharmonisan rumah tangga dalam perspektif Hukum Keluarga Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi lapangan, wawancara mendalam, dan dokumentasi terhadap pasangan suami istri lintas negara, dan tokoh agama setempat. Hasil penelitian menunjukkan bahwa motif utama terjadinya perkawinan antar negara di Sambas meliputi faktor ekonomi, keterbukaan wilayah perbatasan, serta hubungan sosial dan budaya yang telah terjalin sejak lama. Namun, dalam praktiknya, perkawinan antar negara seringkali menghadapi tantangan serius seperti perbedaan budaya, praktik ibadah, kewajiban nafkah, serta status hukum perkawinan yang tidak selalu jelas secara nasional maupun internasional. Dalam perspektif Hukum Keluarga Islam, keharmonisan rumah tangga sangat bergantung pada prinsip mawaddah, rahmah, dan tanggung jawab bersama antara suami dan istri, yang harus dibangun di atas kesepahaman nilai agama dan komitmen yang kuat. Oleh karena itu, regulasi hukum dan pembinaan pranikah lintas negara sangat dibutuhkan agar perkawinan antar negara tidak menjadi sumber konflik, tetapi justru memperkuat ikatan keluarga dan nilai-nilai keislaman di tengah dinamika globalisasi.]